Phase structure, microstructure and electrical properties of BCZT ceramics prepared by seed-induced method - Wasuporn Hirunsit (2018)
© 2016 Trans Tech Publications, Switzerland. The effect of particle sizes of CaZrO3(CZ) nanocrystal on the phase structure, microstructure and electrical properties of Ba0.85Ca0.15Zr0.10Ti0.90O3(BCZT) was studied. CaCO3and ZrO2were used as starting materials for CaZrO3(CZ) seeds synthesized by the molten-salt method. The results found that CZ powder had a pure perovskite phase with particle size about 370 to 460 nm. The CZ-seed were then mixed with the metal oxides BaCO3, CaCO3, ZrO2and TiO2by the mixed oxide method. The phase structure, microstructure and electrical properties of BCZT ceramic were investigated as a function of particle size and concentration of CZ. The results indicated that all samples showed pure perovskite phase. The highest values of density, grain size, dielectric constant (ϵr) and piezoelectric coefficient (d33) were 5.50 g/cm3, 10.95 μm, 2992 and 446 pC/N, respectively which were obtained for the BCZT ceramic doped with CZ-seed particle size of 459 nm.